Comparison of composites containing technical embroidery and woven fabric as reinforcement - Poniecka, Agata; Barburski, Marcin; Angulo, David Ranz; Cuartero, Jesus (Wydawnictwo Politechniki Łódzkiej, 2022)
The following research present a comparison of the strength values of composites containing two types of reinforcements: technical embroidery and woven fabric. Both types of reinforcements were made of flax roving with a linear mass of 400 tex. The technical embroidery was made on a computerized embroidery machine ZSK, type JCZA 0109-550. The use of technical embroidery technology is in line with the idea of sustainable development by minimizing waste generated in the production of composite reinforcements. Tensile strength and tensile elongation tests were carried out. As a result of the conducted research, it was proved that the composite containing the technical embroidery as the reinforcement showed higher tensile strength in the longitudinal direction, compared to the composite containing the fabric as the reinforcement. On the other hand, the composite containing fabric as a reinforcement showed a greater elongation.
Keywords: technical embroidery; composite; woven fabric; sustainable development; haft techniczny; kompozyty; tkana tkanina; zrównoważony rozwój